세포 및 동물모델용 펄스형 전자기장 자극 파라미터 가변장치 설계 및 평가 - 이자우; 박창순; 김준영; 이용흠; Lee, Jawoo; Park, Changsoon; Kim, Junyoung; Lee, Yongheum (Journal of biomedical engineering research, 2022)
An electromagnetic generator with variable stimulation parameters is required to conduct basic research on magnetic flux density and frequency for pulsed electromagnetic fields (PEMFs). In this study, we design an electromagnetic generator that can conduct basic research by providing parameters optimized for cell and animal experimental conditions through adjustable stimulation parameters. The magnetic core was selected as a solenoid capable of uniform and stable electromagnetic stimulation. The solenoid was designed in consideration of the experimental mouse and cell culture dish insertion. A voltage and current adjustable power supply for variable magnetic flux density was designed. The system was designed to be adjustable in frequency and pulse width and to enable 3-channel output. The reliability of the system and solenoid was evaluated through magnetic flux density, frequency, and pulse width measurements. The measured magnetic flux density was expressed as an image and qualitatively observed. Based on the acquired image, the stimulation area according to the magnetic flux density decrease rate was extracted. The PEMF frequency and pulse width error rates were presented as mean ± SD, and were confirmed to be 0.0928 ± 0.0934% and 0.529 ± 0.527%, respectively. The magnetic flux density decreased as the distance from the center of the solenoid increased, and decreased sharply from 60 mm or more. The length of the magnetic stimulation area according to the degree of magnetic flux density decrease was obtained through the magnetic flux density image. A PEMF generator and stimulation parameter control system suitable for cell and animal models were designed, and system reliability was evaluated.